Comparative Analysis of Coupling Relationship Between Land Surface Processes and Atmospheric Boundary Layer Evolution in Nagqu Area in Different Seasons - Guantian WANG; Zeyong HU; Genhou SUN; Yaoxian YANG; Lianglei GU; Chunwei FU; Weiwei FAN; Di WU; Ruijia NIU; Hongyu LUO (Gaoyuan qixiang, 2023)
The coupling relationship between land surface processes and atmospheric boundary layer is one of the key links and difficulties in understanding the thermal effect over the Qinghai-Xizang Plateau.Based on the surface and radiosonde observation data of Nagqu Plateau Climate and Environment Observation and Research Station in May， July and October 2019， this paper analyzes the surface energy budget， the daily and seasonal variations of vertical profile of atmospheric temperature and humidity， in Nagqu Area of the Qinghai-Xizang Plateau， and discusses the evolution law of the atmospheric boundary layer height in different seasons in this region.The results show that the convective boundary layer is 2842 m high in sunny days due to the influence of diurnal net radiation intensity during the observation period in May.It is 1481 m high in cloudy day， which is relatively low， and the strong convective weather may change it into a stable boundary layer.In the meanwhile， the exchange between the sensible heat and the latent heat in the near surface atmosphere provides energy support for the maintenance and development of the atmospheric boundary layer.The vertical profile of potential temperature and specific humidity can correctly reflect the seasonal difference of atmospheric boundary layer height in gqu Area.The height of the convective boundary layer is highest in May， less high in October and the lowest in July while the stable boundary layer is highest in July， less high in May and lowest in October.